L’ultimo capitolo della storia del paesaggio agrario italiano - Lucchesi, Fabio (Ri-Vista. Research for landscape architecture, 2015)
In the years when Emilio Sereni published his “History of italian agricultural landscape”, our country faced maximum intensity of its settlements growth. The specific organization of Italian plains would have soon disappeared forever. The last image of that world has been fixed in GAI aerial survey frames, recently available as a powerful tool for evaluation of landscape changes. Observation of that document disorients for the exceptional degree of alteration; at the same time, however, it should encourage the development of specific technical skills to judge, from time to time, appropriateness, meaning and convenience of transformations.